2019
DOI: 10.35799/pha.8.2019.29307
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Tingkat Kepuasan Pasien Rawat Jalan Terhadap Kualitas Pelayanan Obat Di Instalasi Farmasi Rsud Liun Kendage Tahuna

Abstract: Good service quality will lead to satisfaction in patients. Pharmaceutical services especially in hospitals are sued to realization the expansion of the pharmaceutical service paradigm from product orientation to patient orientation. This study aims to determine the level of outpatient satisfaction to quality of drug service in the Pharmacy Installation of Liun Kendage Tahuna Hospital based on five dimensions of service quality namely tangibles, empathy, reliability, responsiveness, and assurance. This researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
3
1
0
Order By: Relevance
“…The connection of outpatient prescription, inpatient, and emergency rooms is one of the causes of long waiting times. This finding agrees with research by (Nangaro et al, 2019), which has deployed that the reliability dimension has a negative value.…”
Section: Servqual Analysissupporting
confidence: 92%
See 2 more Smart Citations
“…The connection of outpatient prescription, inpatient, and emergency rooms is one of the causes of long waiting times. This finding agrees with research by (Nangaro et al, 2019), which has deployed that the reliability dimension has a negative value.…”
Section: Servqual Analysissupporting
confidence: 92%
“…The overall score of the tangibility dimension shows a negative gap. This finding agrees with (Nangaro et al, 2019), who have discovered several negative gaps in the tangible evidence dimension.…”
Section: Servqual Analysissupporting
confidence: 92%
See 1 more Smart Citation
“…By referring to the SEM analysis, it can be concluded that SEM improves the recommendation for the formulation of the YAPIDA Primary Clinic service quality improvement strategy based on the IPA analysis, namely the YAPIDA Primary Clinic service quality improvement strategy is directed at the four service attributes contained in three dimensions (Nangaro et al, 2019). According to the SEM analysis, the improvement strategy for factor X2 includes "nurse assistance in informing before the service is provided" (X2.3), does not significantly affect Clinical Performance (Erlangga et al, 2020;Musa et al, 2019;Yuliati et al, 2016;Zun et al, 2018).…”
Section: Figure 3 Output Of Sem Analisis Analysismentioning
confidence: 99%